Testing goodness-of-fit for some lifetime distributions with conventional Type-I censoring - Pakyari, Reza; Nia, K. Resalati (Communications in statistics. Simulation and computation, 2017)
A goodness-of-fit test procedure is proposed for some lifetime distributions when the available data are subject to Type-I censoring. The proposed method extends the test procedure of Pakyari and Balakrishnan to other lifetime distributions. The extension to Weibull and log-normal models is studied in details. The new test recovers the nominal level of significance and exhibits more power in comparison to the existing tests for several alternative distributions by means of Monte Carlo simulations. Finally, a real dataset is considered for illustrative purposes.